Technology and the trajectory of myth - Grant, David, 1964- (Elgar studies in legal theory, 2017)
Important and original, this book presents an entirely new way of understanding Technology - as the successor to the dominant ideologies that have underpinned the thought and practices of the West. Like Deity, State and Market, Technology displays the features of a modern myth, promising to deal with our existential concerns by creating a fully empowered sense of the individual on condition of our subjection to it. David Grant and Lyria Bennett Moses examine the dynamics of each of these ideologies, showing how Technology shares their mythological characteristics. They argue that this new myth has not only dominated science to establish its credentials but, utilising robust empirical evidence, they show how law has been imbued with mythological thinking. Demonstrating that law adopts a mythological approach in attempting to regulate technology, they argue that the pathway out of this mythological maze is to establish a new sense of political, corporate and personal self-responsibility. Students and scholars working in the field of emerging technologies and their relationship to politics, corporations, science, law, ethics, and any combination thereof, will find herein a wealth of new directions for their studies. Legal theorists and legal philosophers in particular will find much food for thought in the presentation of this new paradigm.